Recovery and Utilization of Metallurgical Solid Waste - Zhang, Yingyi (IntechOpen, 2019)
At present, a lot of metallurgical solid wastes have not been timely and effectively recycled, resulting in serious problems of environmental pollution and waste of resources. As a result, large-scale comprehensive utilization technologies have been initiated, including slag dry granulation technology, steel slag cement technology, slag wool technology, slag waste heat recovery technology, etc. The comprehensive utilization of metallurgical solid waste has attracted worldwide attention. It is an effective way to improve the utilization efficiency of resources and the added value of products by using scientific metallurgical solid waste recycling methods. This book intends to provide the reader with a comprehensive overview of metallurgical solid wastes comprehensive utilization technology. The comprehensive utilization methods of four representative metallurgical solid wastes are emphatically described, such as blast furnace slag, steel slag, tailings and metallurgical dust.